SNHG10: A Novel Long Non-coding RNA with Multifaceted Roles in Human Cancers - He, Haodong; Yang, Jingjie; Zhou, Yan; Chen, Lihan; Liao, Chuyuan; Gong, Ting; Li, Tongtong; Liu, Haoran; Pan, Yunfei; Zhang, Pengbo; Li, Xiaolan; Yuan, Chengfu (Current Pharmaceutical Design, 2025)
Long non-coding RNAs (lncRNAs) are a type of RNA with a length of more than 200 nucleotides. They do not encode proteins but are crucial in regulating gene expression and affecting the malignant biological behavior of cancer. Small Nucleolar RNA Host Gene 10 (SNHG10) is a novel lncRNA that plays a regulatory role in many malignant tumors. Several recent studies have shown that SNHG10 is aberrantly expressed in various forms of cancer. This instability is closely related to important tumorigenic processes, such as cell proliferation, migration, invasion, epithelial-mesenchymal transition (EMT), and chemotherapy resistance. SNHG10 has been reported to play a role through a variety of molecular mechanisms, including serving as a competing endogenous RNA (ceRNA), regulating epigenetic processes, and affecting immune responses and tumor microenvironment. Furthermore, SNHG10 is involved in metabolic reprogramming, immune evasion, and chromatin remodeling, highlighting its diverse roles in tumor biology. Due to the specificity and selectivity of its expression level, the potential of SNHG10 as a diagnostic biomarker and therapeutic target has attracted significant attention, and its correlation with the prognosis and treatment of various tumor types is of great significance. This review focuses on the biological function and molecular mechanism of SNHG10 and its relationship with various malignant tumors. In addition, this review highlights the potential of SNHG10 to improve precision oncology and develop novel cancer therapies by investigating its upstream regulators, downstream targets, and interactions with nuclear and cytoplasmic processes.
Keywords: biomarker; cell proliferation